Bardoxolone-Methyl (CDDO-Me) Impairs Tumor Growth and Induces Radiosensitization of Oral Squamous Cell Carcinoma Cells - Hermann, Cornelius; Lang, Simon; Popp, Tanja; Hafner, Susanne; Steinritz, Dirk; Rump, Alexis; Port, Matthias; Eder, Stefan (Frontiers in Pharmacology, 2021)
Radiotherapy represents a common treatment strategy for patients suffering from oral squamous cell carcinoma (OSCC). However, application of radiotherapy is immanently limited by radio-sensitivity of normal tissue surrounding the tumor sites. In this study, we used normal human epithelial keratinocytes (NHEK) and OSCC cells (Cal-27) as models to investigate radio-modulating and anti-tumor effects of the synthetic triterpenoid 2-cyano-3,12-dioxooleana-1,9,-dien-28-oic acid methyl ester (CDDO-Me). Nanomolar CDDO-Me significantly reduced OSCC tumor xenograft-growth in-ovo applying the chick chorioallantoic membrane (CAM) assay. In the presence of CDDO-Me reactive oxygen species (ROS) were found to be reduced in NHEK when applying radiation doses of 8 Gy, whereas ROS levels in OSCC cells rose significantly even without radiation. In parallel, CDDO-Me was shown to enhance metabolic activity in malignant cells only as indicated by significant accumulation of reducing equivalents NADPH/NADH. Furthermore, antioxidative heme oxygenase-1 (HO-1) levels were only enhanced in NHEK and not in the OSCC cell line, as shown by immunoblotting. Clonogenic survival was left unchanged by CDDO-Me treatment in NHEK but revealed to be abolished almost completely in OSCC cells. Our results indicate anti-cancer and radio-sensitizing effects of CDDO-Me treatment in OSCC cells, whereas nanomolar CDDO-Me failed to provoke clear detrimental consequences in non-malignant keratinocytes. We conclude, that the observed differential aftermath of CDDO-Me treatment in malignant OSCC and non-malignant skin cells may be utilized to broaden the therapeutic range of clinical radiotherapy.